Antibody Response to SARS-CoV-2 Membrane Protein in Patients of the Acute and Convalescent Phase of COVID-19 - Jörrißen, Philipp; Schütz, Paula; Weiand, Matthias; Vollenberg, Richard; Schrempf, Inga Marie; Ochs, Kevin; Frömmel, Christopher; Tepasse, Phil-Robin; Schmidt, Hartmut; Zibert, Andree (Frontiers in Immunology, 2021)
Understanding the course of the antibody response directed to individual epitopes of SARS-CoV-2 proteins is crucial for serological assays and establishment of vaccines. Twenty-one synthetic peptides were synthesized that have ten amino acids overlap and cover the complete membrane (M) protein. Plasma samples from 32 patients having acute disease and 30 patients from the convalescent phase were studied. Only peptide M01 (aa 1-20) and to a lesser extent peptide M21 (aa 201-222) showed specific reactivity as compared to historical control plasma samples. Peptide M01 was recognized by IgM- (71.9%) and IgG-specific antibodies (43.8%) during the acute phase as early as day 8 PIO. In a longitudinal analysis, a higher reactivity was observed for the IgM response directed to peptide M01 following day 20 PIO as compared to earlier time points of the acute phase. In the convalescent phase, antibody reactivity to the two M-specific peptides was significantly lower (<30% seropositivity). A fusion protein encoding major parts of RBD also showed higher rates of recognition during acute (50.0%) and lower rates in the convalescent phase (23.3%). Taken together, our results suggest that during the acute phase of COVID-19 antibodies are raised to two linear epitopes of the SARS-CoV-2 M protein, located at the very N- and C-termini, showing almost similar levels of reactivity as immunodominant linear epitopes derived from the spike and nucleocapsid protein. Anti-M is also present in the convalescent phase of COVID-19 patients, however at lower levels, with the N-terminus of the M protein as a preferred target.